2004
DOI: 10.1136/bmj.329.7473.1029
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the teaching of evidence based medicine: conceptual framework

Abstract: Although evidence for the effectiveness of evidence based medicine has accumulated, there is still little evidence on what are the most effective methods of teaching it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
81
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(86 citation statements)
references
References 11 publications
2
81
0
3
Order By: Relevance
“…This procedure could be expected because the information given during the evidencebased-medicine course focused on searching in PubMed. However, the instruction on the search file suggested to start with a search for relevant guidelines, which is in line with the latest insight that practitioners should be stimulated to become more users and not so much doers of evidence-based medicine (22). For them, it is not always necessary to search and appraise original articles themselves.…”
Section: Strength and Limitationsmentioning
confidence: 98%
“…This procedure could be expected because the information given during the evidencebased-medicine course focused on searching in PubMed. However, the instruction on the search file suggested to start with a search for relevant guidelines, which is in line with the latest insight that practitioners should be stimulated to become more users and not so much doers of evidence-based medicine (22). For them, it is not always necessary to search and appraise original articles themselves.…”
Section: Strength and Limitationsmentioning
confidence: 98%
“…), intervention (education on clinical research and EBM), and the outcome (objective questionnaire results), our tool was consistent with the Straus conceptual model (Straus et al, 2004). A demographic survey, which specifies gender, age, and profession was also included.…”
Section: Course Evaluationmentioning
confidence: 94%
“…Multiple authors conclude that no one tool would be appropriate to evaluate any proposed EBM training intervention-rather a tool designed to evaluate knowledge acquisition in the domains of intended knowledge gain should be thoughtfully selected (Straus et al, 2004;Shaneyfelt et al, 2006). Straus et al proposed a conceptual framework for the evaluation of EBM that advised considering a physician's "mode of practice" of EBM and choosing an evaluation instrument that reflects the different learners, interventions, and outcomes expected (Straus et al, 2004).…”
Section: Course Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the majority of the studies focused on level 1 and level 2 evaluation to measure learning that occurs separated from the realtime setting of practice. Few studies went beyond level 3 evaluation, which is more difficult to measure because it requires assessment in the practice setting (Straus et al, 2004). However, evaluation of the effectiveness of EBM as an educational intervention should aim to incorporate level 3 and level 4 evaluation into curriculum development to measure the long-term impact of EBM instruction on sustained behavioural changes in a patient care setting and possibly, patient health outcomes.…”
mentioning
confidence: 99%